2020
DOI: 10.1590/s0102-865020200040000006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rosmarinic acid on deformities occurring in brain tissue by craniectomy method. Histopathological evaluation of IBA-1 and GFAP expressions

Abstract: To investigate the role of Rosmarinic acid (RA) in the prevention of traumatic brain injury and the immunohistochemical analysis of IBA-1 and GFAP expressions.Methods: Healthy male rats were randomly divided into 3 groups consisting of 10 rats. Groups were as follows; control group, traumatic brain injury (TBI) group, and TBI+RA group. After traumatic brain injury, blood samples were taken from the animals and analyzed with various biochemical markers. And then IBA-1 and GFAP expressions were evaluated immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It is necessary to emphasize that the approach of bone defects for study of bone healing may be heterogeneous 15 . However, the trauma in order to obtain surgical bed or on craniotomy approach may provide injuries, such as traumatic brain injury, as well as disruption of the blood-brain barrier integrity and the neurovascular unit, culminating in vascular leakage, edema, hemorrhage, hypoxia and neuronal death 16 . According to this premise, Özevren et al 16,17 demonstrated traumatic brain injury when cortical is injured or removed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is necessary to emphasize that the approach of bone defects for study of bone healing may be heterogeneous 15 . However, the trauma in order to obtain surgical bed or on craniotomy approach may provide injuries, such as traumatic brain injury, as well as disruption of the blood-brain barrier integrity and the neurovascular unit, culminating in vascular leakage, edema, hemorrhage, hypoxia and neuronal death 16 . According to this premise, Özevren et al 16,17 demonstrated traumatic brain injury when cortical is injured or removed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the trauma in order to obtain surgical bed or on craniotomy approach may provide injuries, such as traumatic brain injury, as well as disruption of the blood-brain barrier integrity and the neurovascular unit, culminating in vascular leakage, edema, hemorrhage, hypoxia and neuronal death 16 . According to this premise, Özevren et al 16,17 demonstrated traumatic brain injury when cortical is injured or removed. The authors described a variety of pathological factors, such as oxidative stress, the inflammatory response, and apoptosis, as well as enlarged Micrographs A, B, C, D and E demonstrate the pattern of distribution of immunoexpression of OC (brownish color) in the ABG, ABG + PC, ABG + PPP, PPP and control groups, respectively, two weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pure RA-containing products are also available commercially. The diverse biological functions of phenolic compounds like RA can provide various health benefits (Özevren et al 2020 ). RA acts as a powerful anti-oxidant agent mitigating oxidative damage, which could reduce the induction of ROS production via the enhancement of anti-oxidant defense enzymes (Khamse et al 2020 ).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%